2015
DOI: 10.1097/ico.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary, Sulcus-Fixated Intraocular Lens in the Treatment of Spherical and Astigmatic Refractive Errors in Pseudophakic Eyes After Keratoplasty

Abstract: Implantation of a supplementary, sulcus-based IOL is an effective approach to reduce spherical and astigmatic refractive errors in pseudophakic eyes after keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Given that New hydrophilic acrylic supplementary IOL N Reiter et al patients' expectation are quite high for spectacle free vision, this type of secondary intervention offers a valuable alternative for optical enhancement after cataract surgery; whether it be to correct a refractive surprise or to add a premium function such as multifocality or toricity to the primary IOL. [12][13][14][15][16] The study lenses included premium characteristics like diffractive optic (A45D) or extra addition for macular diseases (A45SML), whereas toric features are also commercially available on the same IOL platform. However, the optical properties were not relevant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that New hydrophilic acrylic supplementary IOL N Reiter et al patients' expectation are quite high for spectacle free vision, this type of secondary intervention offers a valuable alternative for optical enhancement after cataract surgery; whether it be to correct a refractive surprise or to add a premium function such as multifocality or toricity to the primary IOL. [12][13][14][15][16] The study lenses included premium characteristics like diffractive optic (A45D) or extra addition for macular diseases (A45SML), whereas toric features are also commercially available on the same IOL platform. However, the optical properties were not relevant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the pupil diameter minimises the higher-order aberrations 2. Secondary sulcus piggyback IOL implantation corrects large refractive errors and has a long safety track record 6 7. Extra focus pinhole IOL addresses both irregular astigmatism as well as pupillary defects.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent results can be obtained by secondary sulcus implantation of piggyback toric IOLs in pseudophakic eyes [ 5 , 9 ]. Meyer and McGhee [ 9 ] demonstrated an uncorrected distance visual acuity changing from 1.2 to 0.3 after a year of follow-up. Thomas et al [ 10 ] demonstrated an astigmatism reduction of 70.95%.…”
Section: Discussionmentioning
confidence: 99%